Characterizing some soil profiles and studying their characteristics and degree of development in the qarandah area – Latakia Governorate - حسن مرح; رقية عادل; غانم سمر (Latakia University Journal -Biological Sciences Series, 2024)
This research, which was conducted in the year 2023, aims to determine some characteristics of the soil formed on limestone rocks spread in the Latakia region as part of a comprehensive study that includes some diagnostic properties of the pedological cover in the southeastern region of the Latakia region and to contribute to its classification. To achieve the objectives of this research, 6 were selected. Soil profiles representative of the studied area were prepared, morphologically described, and the type of vegetation cover and GPS location data were determined for each profile. Samples were taken from the horizons of each profile, and some physical and chemical analyzes were conducted on them (texture, apparent and true density, total calcium carbonate, organic matter content, cation exchange capacity, exchangeable calcium and magnesium, pH) and general chemical analysis of the soil and parent materials. The results of the study of morphological characteristics showed that the profiles are poorly developed and in the early stages of soil formation. The general chemical analysis also showed that the soil is still affected by the composition of the parent rock. The depth of the soil ranged between (95 – 100) cm, and the degree of pH ranged from neutral to basic (7.1, 8.2). The percentage of calcium carbonate increased in the horizons of the profiles, with partial leaching occurring in most of the profiles, especially in the horizons of the P3 profile in which leaching occurred. Almost complete carbonate content, the percentage of organic matter in the surface horizons ranged between (0.682 – 9)%, depending on the availability of suitable conditions for the accumulation of organic matter. As for the cation exchange capacity, it was high (17.82 – 87 mm/100 g) as a result of the high content of organic matter and clay. (14.54, 76.67)%, and It was noted that calcium predominated on the adsorption surface (2.4 - 67.4 mM/100 g), followed by magnesium (1.6 – 16.6 mM/100 g).. From a classification point, the soils were classified under the following orders: Entisols, Mollisols, Xerolls.